1998
DOI: 10.1023/a:1008201331167
|View full text |Cite
|
Sign up to set email alerts
|

Do specialists do it better? The impact of specialization on the processes and outcomes of care for cancer patients

Abstract: Despite the fact that care provided by specialized centres/clinicians appeared to be better both when assessed in relation to process indicators and to mortality, this evidence should be considered far from conclusive because of major methodological flaws in these studies. Relative to current efforts to promote evidence-based policy-making, this review underscores the limited capability of scientific information to provide reliable guidelines for structuring better health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 52 publications
1
46
0
4
Order By: Relevance
“…As for efficiency, for instance, studying the Canadian Province of Ontario, Preyra and Pink (2006) find large scale unexploited gains from consolidation in the hospital sector, while Bilodeau et al (2002), concentrating on Québec, show the presence of both economies and diseconomies of scale, with some establishments operating at constant returns to scale. As for effectiveness, for example, focusing on U.S. surgical procedures, Birkmeyer et al (2002) find that mortality rates are lower the higher the volume of patients treated, whereas Grilli et al (1998) challenge this view, by surveying literature on cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…As for efficiency, for instance, studying the Canadian Province of Ontario, Preyra and Pink (2006) find large scale unexploited gains from consolidation in the hospital sector, while Bilodeau et al (2002), concentrating on Québec, show the presence of both economies and diseconomies of scale, with some establishments operating at constant returns to scale. As for effectiveness, for example, focusing on U.S. surgical procedures, Birkmeyer et al (2002) find that mortality rates are lower the higher the volume of patients treated, whereas Grilli et al (1998) challenge this view, by surveying literature on cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Specialisation as opposed to generalist practice is essential to enhance pharmacists' contribution to patient care considering that pharmacists will have to work with other specialists in multidisciplinary teams and the complex nature of disease and medicines. Although studies comparing the relative impact of specialist and nonspecialist pharmacists in patient care are lacking, a systematic review conducted to assess the impact of care provided to cancer patients by specialists and non-specialist clinicians showed that the patients receiving specialists' care had better health outcomes including reduced mortality rate than those receiving care from non-14 specialists [18]. Pharmacists' specialisation is likely to have a similar impact on patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Subspecialty training is an important part of appropriate surgical management [15][16][17][18]. Although often cited as a reason for the inability to obtain optimal cytoreduction, biologic aggressiveness does not determine cytoreducibility [19][20][21].…”
Section: Discussionmentioning
confidence: 99%